Estudio del arte digital y su relación con los procesos artísticos. - Robles Vega, Jhon Paul (2016)
Humanity has a changing nature, with the passing of the years new trends, new fashions, new methods of living are developed, and there are new methods of conceiving an artistic work. In the same way (guru, sf) within the contemporary artistic discourses, we can show an increase with respect to the development of works not only "beautiful" but also with an ever deeper content since an artist is not only the creative genius who Paints or sculpts in a romantic way for the sake of art, rather since the last century the artist presents himself before society as a thinker, a philosopher bringing a work of art to a much higher status from all senses, aesthetic, critical, Playful, etc. Under this guideline have been an endless number of artistic manifestos with which, has been explored in every field possible in the name of art through large-scale sculptures, expressionism, hyperrealism, cubism, abstract art, Magical realism, but beyond that explored painting techniques are also the styles that go a step further in the evolution of art where performance, object art, happening, land-art, installations. The latter within the field of artistic intervention directly in the specific place where the work has its meaning, its reason for being. In this new technological age we have many advantages over past centuries, since we live in a world where machines have a very important role in the day to day of people, just as artists have taken advantage of this "technology" as A new method to conceive the artistic proposals experiencing in a completely new world generating works or better said artistic techniques as, photography, video art and the so-called "digital arts" in the latter are developed works where the artist Morton Heilin presents us Sensorama , Which is the first work of art that is presented in a completely immersive environment inviting the viewer no longer to look at a painting, but rather to be inside the work and why not be one more element in this creative process. Like this there are countless artists who opted for virtual art as the field of art development itself. And it is in this same field where an immersive work of art is recreated taking advantage of the new technologies of the XXI century and thus is born YOUR EYES MY WORLD that is a work of virtual character, where it is intended to flood a real place with another real place, this will contain Images of places that the spectators most probably do not know taking them in the light of the existence and the recognition of valleys that the own inhabitants pray are hardly known. Virtual reality is mainly used in fields such as medicine, militia, cinema, video game corporations are introducing virtual reality as a new method of visualization of their games offering completely immersive field where the user can immerse themselves in these games, In the same way the film industry from the initiatives of animation in 2D and 3D in which Disney, Pixar, DeamWorks, have been the first ones to take the technologies to give life to characters of the comics, generating thus with a fleet of specialized artist In the animation an aesthetically stylized cinematographic work.